REFLECTIONS IN THE TURKISH PRESS OF THE ISRAELI STATE'S DECISION TO DECLARE JERUSALEM THE CAPITAL - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2019)
Throughout history, the Middle East has been a strategic region of importance for world states. Therefore, the developments in this region, which can be expressed as a crisis center, are also on the agenda of the world states with the domino effect. One of the problems in the Middle East is the Israeli - Palestinian conflict. This conflict between the two societies, based on historical and religious reasons on the same geography, brought with it disagreements and unresolved issues. Important issues of the conflict between Israel and Palestine include border issues, settlements, refugees, security, Palestinian recognition, blockade of world states. Another topic that is the subject of political debate for both communities is the status of Jerusalem. Jerusalem is sacred for both Israel and Palestine. Therefore, both communities see Jerusalem as the capital of the city. The decision that escalated this dispute was the decision of the State of Israel to declare Jerusalem the capital. The law adopted by the Israeli Parliament on July 30, 1980, Jerusalem is the capital of Israel in full and unified. is located. This decision has made it more difficult to reach an agreement between the two communities and has made the position of world states difficult. Because the problem is based not only on political reasons but also on religious and historical reasons. The status of Jerusalem, which is at the center of political, historical and religious debates, is one of the major problems of the world agenda and also naturally carries a special meaning for the Republic of Turkey. Therefore, the decision taken by the Israeli government on the status of Jerusalem has made a major impact in Turkey. This study aims to evaluate the reflections of the Israeli State's decision to declare Jerusalem as its capital from the perspective of the Turkish press, which has caused tension between the two communities and thus has an impact all over the world. The study has been shaped by analyzing the news in the Turkish press about the decision taken by the State of Israel. The newspapers with different publication policies were selected, and the way in which these newspapers evaluated the Jerusalem decision was tried to be put forward.
Keywords: Israeli; Palestinian; Jerusalem,Turkish Press